Isolation of the glycoside from the leaves of Lagerstroemia speciosa (Linne) Pers. Fam. Lythraceae (Banaba) - Racho, Angelito Celso Corsame (Quezon City: College of Pharmacy, University of the Philippines, 1983.)
The isolation of glycosides from the leaves of Lagerstroemia speciosa (Linne) Pers. Fam. Lyrthraceae (locally known as banaba) was done first by a series of extraction using different solvents and second by thin layer chromatography of the different extracts.
​Thesis (Bachelor of Science in Industrial Pharmacy)--University of the Philippines, 198.
Keywords: Lagerstroemia; Banaba